2019
DOI: 10.1002/pc.25095
|View full text |Cite
|
Sign up to set email alerts
|

Boron nitride‐graphene sponge as skeleton filled with epoxy resin for enhancing thermal conductivity and electrical insulation

Abstract: 3D Graphene sponge (GS) supported boron nitride (BN) skeleton (BN@GS) was fabricated through a facile method by using ammonium sulfide under mild conditions. Then, BN@GS sponge was infiltrated by epoxy resin to prepare the composites. The microstructures of BN@GS were controlled by adjusting the mass ratio of GS to BN and the dimension of BN to obtain thermally conductive but electrically insulating polymer composites. The thermal and electrical properties of composites were investigated and the results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[2][3][4][5] Therefore, the development of efficient heat dissipation materials has become an urgent need for the development of integrated circuits. [6][7][8] Polymer composites have attracted much attention because of their good performance, [9][10][11][12][13] including light weight, easy to process and other advantages, but the thermal conductivity of most polymers themselves is not high, only 0.1-0.3 W m À1 K À1 , which cannot meet the heat dissipation requirements of electronic devices. [14][15][16] Therefore, polymer matrix is usually filled with high thermal conductivity fillers to obtain composite materials with high thermal conductivity, and high thermal conductivity fillers is the most important thing to prepare high thermal conductivity polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Therefore, the development of efficient heat dissipation materials has become an urgent need for the development of integrated circuits. [6][7][8] Polymer composites have attracted much attention because of their good performance, [9][10][11][12][13] including light weight, easy to process and other advantages, but the thermal conductivity of most polymers themselves is not high, only 0.1-0.3 W m À1 K À1 , which cannot meet the heat dissipation requirements of electronic devices. [14][15][16] Therefore, polymer matrix is usually filled with high thermal conductivity fillers to obtain composite materials with high thermal conductivity, and high thermal conductivity fillers is the most important thing to prepare high thermal conductivity polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…Although pure graphene networks have great potentials in forming thermally conductive pathways for polymer composites, their low density and relatively weak sheet interconnections would inevitably hinder the further improvement in thermal conductivity of their polymer composites. Thus, functional additives, especially commercially available thermally conductive materials, such as GNPs [ 9 , 77 , 228 ], boron nitride (BN) nanoplatelets [ 229 231 ], carbon nanotubes (CNTs) [ 62 , 232 ], carbon fibers [ 233 ], cellulose nanocrystals [ 234 ], copper nanowires [ 235 ], and silicon carbide nanowires [ 236 ], are usually incorporated into the graphene networks to obtain hybrid graphene networks for enhancing the structural robustness and thermally conductive properties.…”
Section: Preconstruction Of Hybrid Graphene Network and Their Conduct...mentioning
confidence: 99%
“…Additionally, the thermal conductivity of epoxy resin is only about 0.2 W/(m·K), which seriously affects the heat dissipation performance of the device. Some studies have shown that doping a certain amount of thermal conductive fillers in polymers can improve the thermal properties but adding too much filler will cause poor dielectric properties of the materials [ 12 , 13 ]. Therefore, developing new composite insulation materials which offer excellent thermal conductivity but low electrical conductivity has attracted significant interest worldwide [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%